2014
DOI: 10.3324/haematol.2013.101741
|View full text |Cite
|
Sign up to set email alerts
|

Detection and outcome of occult leptomeningeal disease in diffuse large B-cell lymphoma and Burkitt lymphoma

Abstract: Risk of leptomeningeal disease haematologica | 2014; 99 (7) 1229

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
70
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 32 publications
4
70
0
1
Order By: Relevance
“…42,[47][48][49][50] More recent analyses of larger series of CSF-stabilized samples using 4-8 color FCM have confirmed the greater sensitivity of FCM vs. CC with a median proportion of occult CNSL (FCM+/CC-CSF) of 12% (range: 5%-13%) ( Table 1). 10,45,51 Patients with occult CNSL (i.e., CC-and FCM+ CSF) typically showed lower levels of CSF infiltration (<20% or <1 tumor B cell/μL) than FCM+/CC+ cases, 45 further supporting the greater sensitivity of FCM vs. CC. These studies 10,45,51 also showed very few false-negative FCM results (range: 0%-<1%), further supporting its greater diagnostic efficiency with respect to CC.…”
Section: Multiparameter Flow Cytometry Analysis Of Csf Samplesmentioning
confidence: 77%
See 3 more Smart Citations
“…42,[47][48][49][50] More recent analyses of larger series of CSF-stabilized samples using 4-8 color FCM have confirmed the greater sensitivity of FCM vs. CC with a median proportion of occult CNSL (FCM+/CC-CSF) of 12% (range: 5%-13%) ( Table 1). 10,45,51 Patients with occult CNSL (i.e., CC-and FCM+ CSF) typically showed lower levels of CSF infiltration (<20% or <1 tumor B cell/μL) than FCM+/CC+ cases, 45 further supporting the greater sensitivity of FCM vs. CC. These studies 10,45,51 also showed very few false-negative FCM results (range: 0%-<1%), further supporting its greater diagnostic efficiency with respect to CC.…”
Section: Multiparameter Flow Cytometry Analysis Of Csf Samplesmentioning
confidence: 77%
“…10,42,45,46 Early studies analyzing non-stabilized CSF samples by ≤4-color FCM already demonstrated increased sensitivity in between 3% and 20% of cases as compared with cytology (Table 2). 42,[47][48][49][50] More recent analyses of larger series of CSF-stabilized samples using 4-8 color FCM have confirmed the greater sensitivity of FCM vs. CC with a median proportion of occult CNSL (FCM+/CC-CSF) of 12% (range: 5%-13%) ( Table 1).…”
Section: Multiparameter Flow Cytometry Analysis Of Csf Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…The detection of occult leptomeningeal minimal residual disease is possible utilizing flow cytometric techniques and can be a useful tool in identifying those patients who have higher risk of CNS relapse and may benefit from augmented prophylaxis versus those who will not. 11,12 Incorporating liposomal cytarabine into post-HSCT CNS prophylaxis has promise in this regard. With increased utilization both pre-and post HSCT, there will be opportunities to evaluate whether liposomal cytarabine may have a role in either reducing or possibly eliminating the need for cranial boosting during the conditioning regimen prior to HSCT.…”
mentioning
confidence: 99%